FERNS RICHNESS ALONG ENVIRONMENTAL GRADIENTS IN AYER HITAM FOREST, PENINSULAR MALAYSIA (FUDMA JOURNAL OF SCIENCES, 2023)
Fern species richness was assessed to ascertain the distributional pattern of the ferns as influenced by the environmental gradients in Ayer Hitam forest reserve, Peninsular Malaysia. The ferns were collected using a preferential non-random sampling technique. Temperature, humidity, light intensity and elevation data were obtained at each point of collection of the ferns. The influence of these environmental gradients on the distribution of the species was determined using Detrended Correspondence Analysis (DCA) and general linear model (GLM). A total of 67 ferns were identified at all the study sites. Two ferns namely Asplenium antiquum and Pteris longipinnula were first recorded in this study. In all the sites, light intensity ranges from 337.9 – 8098 lux, temperature ranges from 28.5 - 33oC, humidity ranges from 66.24 - 88.80%, and elevation ranges from 14–33m. Tectaria singaporeana and Nephrolepis biserrata are the only species that are widely distributed across all the study sites. The DCA revealed that the light intensity influences the distribution of the ferns species in this forest. However, the GLM showed that temperature had a positive influence on the distribution of the ferns while light intensity had a negative influence on them.
Keywords: Diversity; Ferns; Microclimate; Muar; Peninsular Malaysia; Tectaria singaporeana